2019
DOI: 10.18585/inabj.v11i3.810
|View full text |Cite
|
Sign up to set email alerts
|

WIF1 Qualitative-Methylation from Peripheral Blood Could Not Be Used as Biomarker for The Risk of Nasopharyngeal Carcinoma or Smoking Behavior in Yogyakarta Panel

Abstract: BACKGROUND: Tobacco smoking plays an important role in nasopharyngeal carcinoma (NPC) risk. The Wingless-related integration site (WNT) Inhibitory Factor 1 (WIF1) as one of the tumor suppressor gene (TSG), functions to control cell proliferation through suppression of WNT signaling pathway. WIF1 methylation is one of epigenetic mechanisms which causes overactivated of WNT pathway in NPC development. WIF1 methylation from buffy coat related to smoking status and NPC risk is not known yet.METHODS: This was a nes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In contrary to a meta-analysis conducted by Okekpa et al, (2019), the study showed similar but significant risk of smoking habit among people from Asia (OR 1.41, 95% CI: 1.27-1.57). Previous studies in several regions have shown a significant association of tobacco consumption, including in Indonesia (Amtha et al, 2009;Chang et al, 2017;Nuaba et al, 2020), although some were insignificant (Adoga et al, 2018;Kurniawan et al, 2019). Given a larger population in genetic diversity will present more representative results; however, limited studies and high heterogeneity might explain the difference in the current pooled analysis.…”
Section: Risk Factor For Npc In Indonesiamentioning
confidence: 73%
See 2 more Smart Citations
“…In contrary to a meta-analysis conducted by Okekpa et al, (2019), the study showed similar but significant risk of smoking habit among people from Asia (OR 1.41, 95% CI: 1.27-1.57). Previous studies in several regions have shown a significant association of tobacco consumption, including in Indonesia (Amtha et al, 2009;Chang et al, 2017;Nuaba et al, 2020), although some were insignificant (Adoga et al, 2018;Kurniawan et al, 2019). Given a larger population in genetic diversity will present more representative results; however, limited studies and high heterogeneity might explain the difference in the current pooled analysis.…”
Section: Risk Factor For Npc In Indonesiamentioning
confidence: 73%
“…All these Figure 1. PRISMA Flowchart status analysis included three studies for meta-analysis (Amtha et al, 2009;Kurniawan et al, 2019;Nuaba et al, 2020) (Figure 2). The overall pooled analysis revelaed that smoking increased the odds of NPC, although no statistical emerge as risk factor (OR 4.39, 95% CI: 0.79-24.40) the risk of NPC; however, it was not statistically significant (p=0.09).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated cigarette smoking confers a two- to six-fold higher risk of NPC development, with the risk increasing the longer one is a smoker and the more cigarettes one smokes in a day [ 107 , 108 , 109 , 110 , 111 ]. Cigarette smoke is known to contain carcinogenic compounds that cause DNA damage (genome), recruit DNA methyltransferase, hypoxia, activate DNA-binding proteins, and can eventually lead to genome alteration (mutation), disruption of cellular metabolic processes, and epigenetic change [ 112 , 113 ].…”
Section: Npc Diagnostic Biomarkersmentioning
confidence: 99%
“…The global NPC incidence is 1.7/100,000 per year. Estimated incidence of NPC in Indonesia is quite high, which is 8.3/100,000 per year (1,2). On the other hand, the incidence was rare in Europa and America.…”
Section: Introductionmentioning
confidence: 98%